Comparative study of pedaling and gait, related to the physical medical programmes and rehabilitation - A. Villarroya; S. Nerín; E. Serrano; T. Moros; C. Marco; L. P. Rodríguez (European Journal of Human Movement, 2010)
We have done a study in healthy, young adult volunteers by filming their pedalling and gait and the electromyography of the main muscles of the lower limb. The gait analyse was divided in 7 phases and the pedalling in 8 sectors. The results show that the range of motion in flexion of the hip and knee joints is larger during pedalling than during stepping and in the ankle is larger in extension. The mean muscular activity is larger during pedalling than during the gait being statistically significant in the gluteus maximus (27.4%± 8,5 when pedalling and 11.3%± 7.8º during gait. p< 0.05). And in the cuadriceps: rectus femoris (21.3%± 5.9 during pedalling and 6.5% ± 3.3 with pedalling and. p<0.05). Vastus medialis (26.2% ± 9 with pedalling and 10.1% ± 7.6 with gait. p<0,01). The maximal activity of each muscle excepting tibialis anterior and hip adductors is longer during pedalling than during gait being significant in the cuadriceps or rectus femoris (37.0% ± 12,1 in the sectors 1 and 2 and 12.4% ± 8.1 in phases A and G. p< 0,05 of pedalling and gait); Vastus medialis (48.4% ±10.8 sectors 1 and 2 and 16.7% ± 7.1 in phases A and G. p<0.05 of pedalling and gait). We consider the usefulness of pedalling in the programs of Physical Medicine and Rehabilitation to achieve a larger range of joint movement with less over stress and charge and the respons of the muscular efficacy with submaximal activities and without changing the heart rate. KEY WORDS: Cycling. Pedalling. Gait. Biomechanics. Electromyography.